2017
DOI: 10.1159/000481535
|View full text |Cite
|
Sign up to set email alerts
|

Subconjunctival PRGF Fibrin Membrane as an Adjuvant to Nonpenetrating Deep Sclerectomy: A 2-Year Pilot Study

Abstract: Purpose: To evaluate the potential role of the autologous PRGF (plasma rich in growth factors) fibrin membrane in tissue regeneration after glaucoma filtering surgery. Materials and Methods: Ten patients with medically uncontrolled primary open-angle glaucoma underwent nonpenetrating deep sclerectomy and were treated with PRGF fibrin membrane as adjuvant. Intraocular pressure reduction was the primary outcome. This variable was measured preoperatively and also at each follow-up visit. Secondary outcomes includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…The 5 conditions include: injecting E-PRP into anterior chamber to treat keratoconus hydrops (one case), 50 intracameral E-PRP injection to treat ocular hypotension post glaucoma surgery (one case), 51 using PRP from blood bank to mix with other materials to form a moldable paste to reconstruct orbital floor fracture (10 cases), 52 injecting autologous PRP to treat retinitis pigmentosa (37 patients), 53 and using PRGF fibrin membrane to treat medically uncontrolled primary open angel glaucoma (n=10). 54 All these studies reported positive outcomes with significant improvement in clinical signs and symptoms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 5 conditions include: injecting E-PRP into anterior chamber to treat keratoconus hydrops (one case), 50 intracameral E-PRP injection to treat ocular hypotension post glaucoma surgery (one case), 51 using PRP from blood bank to mix with other materials to form a moldable paste to reconstruct orbital floor fracture (10 cases), 52 injecting autologous PRP to treat retinitis pigmentosa (37 patients), 53 and using PRGF fibrin membrane to treat medically uncontrolled primary open angel glaucoma (n=10). 54 All these studies reported positive outcomes with significant improvement in clinical signs and symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…Significant improvement in visual field, multifocal electroretinography and microperimetry values at follow-up. Rodriguez-Agirretxe et al 2018 54 Prospective, non-randomized, non-comparative, interventional case series (Level IV) Primary open angle glaucoma 10 No mPRGF Single application 24 months Statistically significant reduction in IOP Ocular surface regeneration following glaucoma surgery. Abdalrahman et al 2019 51 Case report (Level VI) Ocular hypotension post glaucoma surgery non-responsive to treatment 1 No E-PRP injection Single injection 6 months Improved intraocular pressure Stable clinical signs at final follow up Alio et al 2019 50 Case report (Level VI) Keratoconus hydrops 1 No Autologous E-PRP injection Single injection 6 months Clinical signs resolved by 1 week Stability through 6 months.…”
Section: Methodsmentioning
confidence: 99%
“…The IOP also showed a significant improvement (p < 0.027), results similar to those obtained in other PRGF related studies, 8,10,25 being some of these directly or indirectly related to glaucoma. 27 Further studies may be beneficial to clarify the role of PRGF for the management of the IOP and its clinical applications.…”
Section: Discussionmentioning
confidence: 99%
“…The biological properties of PRGF would theoretically be of great help in reducing fibrosis after NPDS. Rodriguez-Agirretxe et al [12], in a pilot study, evaluated a case series of 10 eyes that underwent NPDS with a PRGF clot inserted in the subconjunctival space. The authors concluded that PRGF might enhance surgery success rates and reduce the need for postoperative medications.…”
Section: Introductionmentioning
confidence: 99%